The relationship between nutritional status and prealbumin levels in children with loss of appetite and iron deficiency: a prospective cross-sectional study - Okuyan, Ömer; Durmus, Sinem; Uzun, Hafize (Frontiers in Nutrition, 2025)
BackgroundPrealbumin, a hepatic protein with a short half-life, has emerged as a sensitive biomarker for assessing nutritional status. This study aimed to evaluate the relationship between nutritional status and prealbumin levels in children experiencing loss of appetite due to iron deficiency and to compare the diagnostic value of prealbumin with established nutritional indices.MethodsA total of 260 children aged 2–15 years were enrolled and categorized into four groups: control (n = 65), appetite loss only (n = 65), iron deficiency only (n = 65), and both conditions (n = 65). Nutritional status was assessed using laboratory biomarkers and indices such as the Controlling Nutritional Status (CONUT) score, Prognostic Nutritional Index (PNI), and Nutritional Risk Index (NRI). Prealbumin levels were measured using the enzyme-linked immunosorbent assay (ELISA).ResultsPrealbumin levels were significantly lower in all patient groups than in controls (p < 0.001). Prealbumin showed strong positive correlations with total cholesterol (r = 0.528), albumin (r = 0.489), and PNI (r = 0.489), and a strong negative correlation with the CONUT score (r = −0.546) (all p < 0.001). ROC analysis demonstrated that prealbumin had high diagnostic accuracy in distinguishing appetite loss (AUC = 0.911) and iron deficiency (AUC = 0.892). Logistic regression confirmed that prealbumin was significantly associated with both conditions (p < 0.001), whereas other indices (CONUT, PNI, and NRI) were not.ConclusionWhile appetite loss is a clinically reported symptom, reduced prealbumin levels reflect the underlying nutritional impact of this condition. Prealbumin is a sensitive and reliable biomarker for assessing nutritional deterioration associated with both appetite loss and iron deficiency in children and outperforms commonly used nutritional indices. Its use may improve early recognition and management of nutritional risk in pediatric populations. Further research is needed to explore the diagnostic and prognostic value of nutritional indices (CONUT, PNI, and NRI) in children.